Faktor Lingkungan yang Berpengaruh Terhadap Kejadian Infeksi Virus Dengue (Studi Kasus Di Kota Semarang) - Muslim, Azhari (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACT Dengue virus infection can show variation of clinical spectrum from mild degree to severe degree. Mild dengue virus infection cause asymptom or fever without unclear causal factor through are followed by dengue fever, dengue haemorrhagic fever and dengue shock syndrome. Dengue virus infection  is an endemic and make potentially outbreaks in all around the world, included in Semarang. Risk factors that influenced on dengue infection, such as host, agent and environment. Host factor consists of gender, nutritional status and age. Role of environment as disease reservoir that Aedes aegypti larvae and mosquitos population depend on existence of places their appropriate habitat.  The objective of this study is to analyze environmental factor that influences on occurence of dengue virus infection.  This is a case control study using 54 cases and 54 controls. Case is appeared by Immunoglobulin G (+) and  control is appeared  by Immunoglobulin  G (-). Risk factors included in this study were physical environment, non physical environment and intrinsic factor. Multiple logistic regression was used to analyze the data. Risk factors of dengue virus infection  in Semarang City were low nutritional status,  the existence  of  larvae in the water  container  and the interval of cleaning water container more  than 7 days.   Keywords : Risk factor, dengue virus infection, environment, Semarang